1988
DOI: 10.1063/1.341908
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization process of Sb-Te alloy films for optical storage

Abstract: Sb-Te alloy films are developed as rewritable optical recording materials based on amorphous crystalline phase transformations. The crystallization process of Sb-Te sputtered films is systematically studied through measurement of recording characteristics to solve the trade-off problem between data (amorphous) stability and erasing sensitivity. Sb2Te3 is shown to be the best practical phase change medium, having room-temperature stability in amorphous states, short erasing times, and potentially good reversibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(31 citation statements)
references
References 8 publications
3
28
0
Order By: Relevance
“…If chemical control prevails over cortical influence on the respiratory controller, as typically occurs during sleep, patients become apneic until Pa C O 2 rises again above the apnea threshold. Thus, the alternating pattern of apnea and hyperpnea continues due to oscillations of the Pa C O 2 around the apnea threshold [52,53]. This periodic respiratory over- and undershoot causes additional sympathetic stimulation in patients who are already sympathetically stimulated through their heart failure [54].…”
Section: Pathophysiology Of Csrmentioning
confidence: 99%
“…If chemical control prevails over cortical influence on the respiratory controller, as typically occurs during sleep, patients become apneic until Pa C O 2 rises again above the apnea threshold. Thus, the alternating pattern of apnea and hyperpnea continues due to oscillations of the Pa C O 2 around the apnea threshold [52,53]. This periodic respiratory over- and undershoot causes additional sympathetic stimulation in patients who are already sympathetically stimulated through their heart failure [54].…”
Section: Pathophysiology Of Csrmentioning
confidence: 99%
“…2 In addition to the well known GST composition, the Sb:Te binary compositions are also known phase change materials. 5 The appreciation of bismuth's mechanism in Sb:Te compounds could aid the understanding in the somewhat more complex Bi doped ternary systems. The Sb 2 Te phase shows a wide compositional tolerance with Sb content ranging from 63 to 81 at.…”
mentioning
confidence: 99%
“…The crystallization of amorphous chalcogenide films has been proven by other researchers to be a process involving nucleation and growth. 16,22,30) The secondary phase precipitated in the early stage can be expected to enhance the heterogeneous nucleation but the higher crystallization temperature of the AIST film reveals that crystallization may be more difficult for the movement of Ag and In atoms in the amorphous matrix. It is believed that the formation of a small amount of AgSbTe 2 phase slightly affected the activation energy and thus, crystallization rate of the amorphous AIST film.…”
Section: Electrical Properties Of Aist and St Filmsmentioning
confidence: 99%
“…The nucleation and growth of -Sb phase can be easy because the literature has reported that there is little volume fraction change associated with the formation of a nucleus for crystallization, and less strain and surface energy need to be overcome when a nucleus grows from the amorphous matrix. [30][31][32] The crystallization rates of amorphous AIST and ST films can be expected to be small and be close to each other because the same major phase (-Sb) is formed. The similar activation energy obtained in Fig.…”
Section: Electrical Properties Of Aist and St Filmsmentioning
confidence: 99%